2013
DOI: 10.1094/phyto-01-13-0013-r
|View full text |Cite
|
Sign up to set email alerts
|

Selection Pressure and Founder Effects Constrain Genetic Variation in Differentiated Populations of Soilborne Bymovirus Wheat yellow mosaic virus (Potyviridae) in China

Abstract: To study the population genetic structure and forces driving the evolution of Wheat yellow mosaic virus (WYMV), the nucleotide sequences encoding the coat protein (CP) (297 sequences) or the genome-linked virion protein (VPg) (87 sequences) were determined from wheat plants growing at 11 different locations distributed in five provinces in China. There were close phylogenetic relationships between all sequences but clustering on the phylogenetic trees was congruent with their provenance, suggesting an origin-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 75 publications
2
14
0
Order By: Relevance
“…All coat protein domains tested were found to be under extreme purifying selection, an observation already reported for members of the Secoviridae [14][16] and other plant-infecting RNA viruses [44][47]. It has been suggested that such extreme purifying selection is a result of selection constraints imposed by specific molecular interactions during vector transmission [47], [48].…”
Section: Discussionsupporting
confidence: 57%
“…All coat protein domains tested were found to be under extreme purifying selection, an observation already reported for members of the Secoviridae [14][16] and other plant-infecting RNA viruses [44][47]. It has been suggested that such extreme purifying selection is a result of selection constraints imposed by specific molecular interactions during vector transmission [47], [48].…”
Section: Discussionsupporting
confidence: 57%
“…The site at Yantai was mostly infested with WYMV, but Chinese wheat mosaic virus (CWMV), an unrelated virus (genus Furovirus, family Virgaviridae) transmitted by the same vector (Diao et al, 1999), was occasionally detected, while only WYMV was detected in Xiping and Yangzhou. There are known to have differences between these WYMV populations (Sun et al, 2013). N12-1 was highly resistant to WYMV in Yantai, Xiping and Yangzhou; a small number of transgenic plants developed disease symptom in Yantai, which is due to the CWMV infection (detected by ELISA).…”
Section: Wymv Resistance Of the Transgenic Wheat In Field Trialsmentioning
confidence: 99%
“…It is clear that studying the genetic variation and evolution of plant viruses proposes an important strategy for agricultural production due to the warming climate and the harsh ecosystem [810]. Evolution analysis of RNA viruses was achieved by codon usage bias, phylogenetic tree, genetic distance, selection pressure, genetic differentiation and gene flow which have been examined in some ss-RNA viruses [11,12] and ds-RNA viruses [4,13]. However, evolutionary analysis has only been conducted in a few viruses with overlapping open reading frames (ORFs).…”
Section: Introductionmentioning
confidence: 99%